Talent management strategies of a public uae hospital in the industry 4.0 ERA: A qualitative analysis - Al Amiri N.; Shawali A.A. (LLC CPC Business Perspectives, 2023)
Talents play a critical role in achieving organizational strategic goals and a higher level of performance in the healthcare industry. Therefore, the UAE government, which strives to provide world-class healthcare services, encouraged the adoption of talent management strategies and creation of essential capabilities for talent recruitment, development, and retaining. This study explores the talent management strategies, policies, and practices in multiple departments of a public UAE hospital. Moreover, it investigates required skills, competencies, and programs for those departments in the context of Industry 4.0. The study adopted a case study approach and qualitatively surveyed a purposive sample of 13 departmental managers, section heads, and supervisors who are experienced in employee management. The study found that talent management at the studied hospital is undefined and unclear in terms of strategies, policies, and practices. Furthermore, the study highlighted the need for employee encouragement, motivation, and engagement, as well as confirmed the critical role of management and leadership in facilitating talent management in the hospital. Accordingly, a UAE hospital could benefit from this study to develop its talent management policy and strategies that will guide managers in the Industry 4.0 era. Nabeel Al Amiri, Ahlam Abu Shawali, 2021.